2005
DOI: 10.1515/hf.2005.070
|View full text |Cite
|
Sign up to set email alerts
|

Differences in acoustic velocity by resonance and transit-time methods in an anisotropic laminated wood medium

Abstract: The influence of inhomogeneity on acoustic velocity measured by a resonance-based WoodSpec acoustic tool and a transit-time-based Fakopp-2D tool was investigated. Four laminated panels with different degrees of inhomogeneity were prepared and acoustic velocities were measured using both tools. Velocities measured by the Fakopp-2D tool were always higher than those measured by the WoodSpec tool in all panels. The difference in the two velocities was found to vary depending on the magnitude of inhomogeneity. It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 2 publications
0
16
0
Order By: Relevance
“…It is well known that speed of stress wave pulse depends on the Young's modulus and density of the material. Chauhan et al (2005) have shown that acoustic velocity by longitudinal vibration is the function of the volume weighted average stiffness of the entire sample under the test. Therefore, DMoE from resonance frequencies (longitudinal or flexural vibrations) remain unbiased from the localized variations within the sample and are more close to the static MoE.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that speed of stress wave pulse depends on the Young's modulus and density of the material. Chauhan et al (2005) have shown that acoustic velocity by longitudinal vibration is the function of the volume weighted average stiffness of the entire sample under the test. Therefore, DMoE from resonance frequencies (longitudinal or flexural vibrations) remain unbiased from the localized variations within the sample and are more close to the static MoE.…”
Section: Resultsmentioning
confidence: 99%
“…Divos and Tanaka (2005) reported the effect of frequency of measurement on determination of modulus of elasticity and found higher MoE with increasing frequencies. Chauhan et al (2005) reported 4% to 26% difference in acoustic velocity measured by resonance and transit time tool in laminated wood panels with different magnitude of in-homogeneity which in turn represent 8% to 52% difference in their DMoE. The difference was attributed to the mechanism of wave propagation in anisotropic wood medium.…”
Section: Introductionmentioning
confidence: 96%
“…The dynamic modulus of elasticity (MOEd - Urhan et al 2014) can be estimated from the velocity of acoustic waves (acoustic velocity, CT) passing through the wood, according to the following formula (eqn. 2): (2) where WD is the wood density, expressed in kg m -3 , and AV is the velocity in km s -1 (Pellerin & Ross 2002, Chauhan et al 2005, Lasserre et al 2007). Wood density was determined by volumetric methods, which required measuring the volume and mass of dry wood in the laboratory.…”
Section: The Modulus Of Elasticity Equationmentioning
confidence: 99%
“…It has been suggested this technique provides MOE measurements, which are an average through the cross-section of the log. 124,159,174 This has been associated with the fact that it uses an acoustic signal that has propagated many times through the length of the log due to multiple reflections from each end. However, there are a few factors that have been suggested as potential sources of errors in resonance measurements.…”
Section: Fakoppmentioning
confidence: 99%